Translation and cultural adaption of Observer OPTION5 and OPTION12 in a Danish context - Bettina Mølri Knudsen; Karina Olling; Karina Dahl Steffensen (Health Literacy and Communication Open)
Background and aim The aim of this study was to translate and culturally adapt the Observer scales OPTION5 and OPTION12 into Danish to improve the accessibility of the scales for all healthcare professionals and patients as co-researchers to objectively assess the process of shared decision making (SDM) in consultations, communication training and research.Methods The translation process was systematically planned and conducted using Beaton’s guidelines, including forward and backward translation, expert review, and pre-testing. Pre-testing involved 17 informants with different experiences in rating and perspectives.Results Feedback from informants indicated high usability and potential of the OPTION5 and OPTION12 observer scales in assessing SDM behavior. Adjustments were made to improve clarity and readability.Discussion In summary, the adaptation and validation of the Observer OPTION5 and OPTION12 scales for use in Denmark proved to be successful and a valuable tool for objective assessment of the SDM process in patient-clinician encounters. Future research should focus on evaluating the psychometric properties of both scales. The availability of validated Danish versions holds promise for advancing the use of the scales for objective assessment of SDM in consultations, research and communication training and for promoting the use of both scales in non-academic, clinical settings.